Evidence for a Causal Association Between Human Cytomegalovirus Infection and Chronic Back Pain: A One‐Sample Mendelian Randomization Study - Maryam Kazemi Naeini; Maxim B. Freidin; Isabelle Granville Smith; Stephen Ward; Frances M. K. Williams (JOR Spine, 2025)
ABSTRACT Background Chronic back pain (CBP) is a major cause of disability globally. While its etiology is multifactorial, specific contributing genetic and environmental factors remain to be discovered. Paraspinal muscle fat has been shown in human and preclinical studies to be related to CBP. One potential risk factor is infection by cytomegalovirus (CMV) because CMV is trophic for fat. CMV may reside in the paraspinal muscle adipose tissue. We set out to test the hypothesis that previous CMV infection is linked to CPB using a one‐sample Mendelian randomization (MR). Method The sample comprised 5140 UK Biobank participants with information about CMV serology and CBP status. A one‐sample MR based on independent genetic variants predicting CMV positivity was conducted in Northern European participants. To validate the association further, the MR study was repeated using a CMV polygenic risk score (PRS). As a negative control for confounding and spurious causal inference, we used Epstein–Barr virus (EBV) serology, because EBV is another common viral infection but is not trophic for adipose tissue. Results A genome‐wide association study for CMV seropositivity revealed 86 independent SNPs having p‐value < 2×10−4 that have been used to define genetically‐predicted categories of CMV infection risk. The CMV predicted categories were found statistically significantly associated with CBP (OR = 1.150; 95% CI: 1.005–1.317, p‐value = 0.043). Stronger significant results were obtained using the PRS for CMV seropositivity (OR = 1.290; 95% CI: 1.133–1.469, p‐value = 12E‐4). No such association was seen between EBV and CBP. Conclusion Our results provide evidence for a causal relationship between CMV infection and CBP. Further investigation is warranted to get insight into the mechanism by which CMV might contribute to the pathogenesis of CBP.